The Effect of Inquiry Methods Implementation in Civic Education Subject Towards The Learning Results and Interests for Guidance and Counseling Students in Hamzanwadi University - Dukha Yunita Sari (Simposium Antar Bangsa Seminar dan Workshop)
Educators or in this case are lecturers or teachers have to concern about an effort of increasing students' mastery towards subject matter,some of which are by improving teaching and learning processes. The success of a student in mastering a subject while it is determined by the internal factors of students, such as the level of intelligence, craft, and perseverance, it is also determined by external factors, including the effectiveness of strategies and learning methods used during the teaching. The purpose of this study was to find out whether the application of inquiry methods can influence the results and learning interest of the second semesterof Civic Education subject at Counseling and Education Study Program. The benefits in this study were expected that the results can be further scientific study both for the researchers themselves and for other educators, so that there is an increase in the quality of education, especially in the efforts to improve student learning outcomes and interests. Based on the problems and studies above, the hypotheses in this study were: 1. Ha: there is an influence of the inquiry method application on learning outcomes in the subject of Civic Educationfor the second semester of the counseling study program; 2. Ha: there wasan influence of the inquiry method application on the learning interest in the Civic Education courses in the second semester students of the Guidance and Counseling study program. Based on the results obtained, It was clear that inquiry method succeeded in improving student learning outcomes because inquiry methods more interesting to learn than the lecturing method. Interest test results show that students' learning interest with inquiry methods was higher than the lecture method.